PENERAPAN METODE DEMONSTRASI BERBANTUAN MEDIA AUDIOVISUAL BERUPA VIDEO DALAM MENINGKATKAN HASIL BELAJAR IPAS PADA SISWA - Patmawati, Patmawati; Hasan, Jhems Richard; Erwinsyah, Alfian (DIRASATUL IBTIDAIYAH, 2024)
AbstractThe expected aim of conducting this research is to determine the application of the demonstration method assisted by audiovisual media in the form of video in improving student learning outcomes in Class IV Science and Technology subjects at SDN 9 Limboto. The type of research used in this research is the classroom action research approach. Classroom action research is research where the root of the problem arises in the classroom and is known to the teacher. This research was conducted to improve or overcome problems encountered during the learning process. Students in following the learning process using demonstration methods assisted by audiovisual media in the form of videos show positive results. The results of this research show that student learning outcomes in science and science subjects have increased after going through the demonstration method assisted by audiovisual media in the form of videos which can be seen from the pre-test average score of 57.68 with a learning completion percentage of 37%, test questions in cycle I average score- an average of 64.56 with a learning completeness percentage of 56%, up to the second cycle test questions the average score was 76.68 with a learning completeness percentage of 87%. The application of the Demonstration Method Assisted by Audiovisual Media in the form of Video can improve the learning outcomes of class IV students in the science and sciences subject at SDN 9 Limboto. The recommendation that can be taken from this research is to support the implementation of demonstration methods assisted by audiovisual media in the learning context. Keywords: Demonstration Method Assisted; Audiovisual Media in the Form of Video; Improving Learning Outcomes.